2012
DOI: 10.1016/j.jcf.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and growth factor response to continuous and intermittent exercise in youth with cystic fibrosis

Abstract: HIIE was a sufficient stimulus to increase GH in children with CF, without affecting systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Overall, these data suggest that children may be more prone to free radical generation and as such more sensitive to changes in their redox status in response to exercise despite a smaller skeletal muscle damage and neutrophil mobilization. This response may partly be explained by increases of growth hormone following acute exercise [62,63,64] which seems to be implicated in neutrophil mobilization since in vitro studies have identified its receptors on these immune cells [65]. One may argue that growth hormone increase following exercise is higher in adults in absolute terms, however children experience a greater relative growth hormone rise from its resting values [45], probably as a part of the overall anabolic mechanism supporting their growth and development [61].…”
Section: Responses To Acute Exercisementioning
confidence: 99%
“…Overall, these data suggest that children may be more prone to free radical generation and as such more sensitive to changes in their redox status in response to exercise despite a smaller skeletal muscle damage and neutrophil mobilization. This response may partly be explained by increases of growth hormone following acute exercise [62,63,64] which seems to be implicated in neutrophil mobilization since in vitro studies have identified its receptors on these immune cells [65]. One may argue that growth hormone increase following exercise is higher in adults in absolute terms, however children experience a greater relative growth hormone rise from its resting values [45], probably as a part of the overall anabolic mechanism supporting their growth and development [61].…”
Section: Responses To Acute Exercisementioning
confidence: 99%
“…However, in people with CF, this type of exercise training is burdensome, adding to the already high daily treatment burden, and may not be the most appropriate option due to several factors, including a ‘lack of time’ [ 25 ] and intolerable symptoms of breathlessness and muscle fatigue experienced during continuous exercise [ 26 ]. Furthermore, oxygen desaturation is more likely during moderate intensity continuous exercise [ 27 ], and this type of training may augment inflammation in this population compared to interval training [ 28 ]. An alternative training approach, such as low-volume high intensity interval training (HIIT), may be a more achievable and efficient method to optimise exercise capacity in this population [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have considered the impact of duration and mode (continuous vs. intermittent) of exercise on immune function [8,25,26,40,41]. Hence, we focused in this study on surrogate outcomes as markers of inflammation and skeletal muscle recovery (i. e., leukocytes, IL-6, IL-10) after a single bout of maximal exercise, with different models (short-term high-intensity exercise and long-term high-intensity exercise) and their responses during a 24 h recovery period.…”
Section: Introductionmentioning
confidence: 99%